2015
DOI: 10.4103/0366-6999.163382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Positive Airway Pressure Therapy on Glycemic Excursions and Insulin Sensitivity in Patients with Obstructive Sleep Apnea-hypopnea Syndrome and Type 2 Diabetes

Abstract: Background:For patients with obstructive sleep apnea-hypopnea syndrome (OSAHS) and type 2 diabetes mellitus (T2DM), the night sleep interruption and intermittent hypoxia due to apnea or hypopnea may induce glycemic excursions and reduce insulin sensitivity. This study aimed to investigate the effect of continuous positive airway pressure (CPAP) therapy in patients with OSAHS and T2DM.Methods:Continuous glucose monitoring system (CGMS) was used in 40 patients with T2DM and newly diagnosed OSAHS. The measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Guo et al . [26] found that CPAP therapy may improving both blood glucose and insulin sensitivity in patient with diabetes and sleep apnea-hypopnea syndrome. Several mechanisms can interpret these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al . [26] found that CPAP therapy may improving both blood glucose and insulin sensitivity in patient with diabetes and sleep apnea-hypopnea syndrome. Several mechanisms can interpret these associations.…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis model assessment of IR (HOMA-IR) was calculated using the following the formula: FINS (μg/ml) × FBG (mmol/L)/22.5. [ 15 ] Rats were subsequently subjected to an oral glucose tolerance test (OGTT) with glucose (2 g/kg, body weight [bw]) after fasting overnight (12 h). One week after the OGTT, an intraperitoneal insulin tolerance test (IPITT) with insulin (0.75 U/kg bw) was also performed after fasting for 7 h. Plasma glucose levels were measured by ACCU-CHEK Active Monitor (Roche Diagnostics, Basel, Switzerland) at 0, 30, 60, 90, and 120 min, and the area under the curve (AUC) was calculated.…”
Section: Ethodsmentioning
confidence: 99%
“…To date, the effect of CPAP on GV determined by CGM in type 2 DM patients has been examined in five studies [ 22 25 , 42 ]. A significant reduction in GV that was assessed by MAGE or SD after CPAP treatment was reported by Pallayova et al [ 23 ] and Guo et al [ 24 ] but not by the other investigators [ 22 , 25 , 42 ]. Pallayova et al reported that SD and %CV were decreased rapidly with the initiation of CPAP therapy (i.e., during a CPAP titration night) [ 22 ].…”
Section: Discussionmentioning
confidence: 78%
“…Pallayova et al reported that SD and %CV were decreased rapidly with the initiation of CPAP therapy (i.e., during a CPAP titration night) [ 22 ]. In a study by Guo et al [ 30 ], 30 days of CPAP reduced MAGE and SD by 29% and 27%, respectively, in addition to reduction of HbA1c from 8.70% to 6.95% [ 24 ]. In the present study, adherence to CPAP was adequate (> 4 h/night), and the duration of CPAP was about 3 months.…”
Section: Discussionmentioning
confidence: 99%